Comparative morphology of the epiphyses of Dilophonotini Burmeister, 1878 and Philampelini Burmeister, 1878 (Lepidoptera: Sphingidae) - Ancajima Alcalde, Georgette Paola (2021)
Descargue el texto completo en el repositorio institucional de la Universidade de São Paulo: https://doi.org/10.11606/D.38.2021.tde-19052021-143817